Kinesthetic Guidance for People with Mental Disorders at Balai Persinggahan Sosial Margo Widodo - Firdaus, Danang; Murtadho, Ali (PT Hakhara Akademia Indonesia, 2025)
This study aims to examine the implementation of kinesthetic guidance as an innovative rehabilitation intervention for individuals with mental disorders (ODGJ) at BPS Margo Widodo. The primary challenge addressed is the limitation of conventional, monologic guidance methods, which result in low participant engagement and reduced responsiveness to the material. A descriptive qualitative approach used field studies through participatory observation and in-depth interviews with staff and beneficiaries. The findings indicate that integrating physical activity into the guidance process significantly enhances participants' motivation, focus, and emotional stability. Applying kinesthetic guidance, which emphasises direct movement and interactive communication, creates a more dynamic learning environment and supports the development of cognitive and affective abilities among ODGJ. These results suggest that this innovative approach may serve as an effective alternative in the mental health rehabilitation of special groups. Consequently, the study is expected to contribute strategically to the development of policies and practices that are more responsive and adaptive to the needs of individuals with mental disorders in Indonesia.